To systematics of the genus Saetheria Jackson (Diptera, Chironomidae) from the Russian Far East - Orel, Oksana V. (Zootaxa, 2014)
The genus Saetheria Jackson from the Russian Far East is reviewed. The males of S. reissi Jackson, 1977, S. tamanipparai (Sasa, 1983) and S. tylus (Townes, 1945) are redescribed and figured. The pupa of S. reissi is redescribed and illustrated. The larva of S. reissi Jackson is described for the first time. Comments on the systematics and distribution of each species are provided. Paracladopelma kisopediformis Sasa, Kondo, 1993 is designated a new junior synonym of S. reissi Jackson, 1977. Keys to the males, pupae and larvae of the Russian Saetheria are given.